A preliminary identification of genomic loci for body colour variation in the sea cucumber Apostichopus japonicus. (15th December 2019) - Ge, Jianlong; Tan, Jie; Li, Fenghui; Chen, Siqing; Liu, Changlin; Bian, Li
Abstract: The sea cucumber Apostichopus japonicus is one of the most economically important aquaculture species in China, which shows a distinct characteristic of body colour variation. A number of purple variants were obtained in the coast of China, which shows great potential to develop a niche market. In the present study, to understand the genetic basis of green‐purple colour variation, a genome‐wide association study based on the 2b‐RAD sequencing was conducted. As a result, 8, 795 genome‐wide single nucleotide polymorphism (SNP) markers were obtained and then applied to the association analysis. Ten most associated SNP loci with p ‐value <1.0 × 10 –8 were obtained, and they were assigned to 4 chromosomes (chr17, chr21, chr15 and chr05). In genomic regions neighbouring to those SNPs, 33 candidate genes with annotation were obtained and the endothelin‐converting enzyme‐1, which was reported to be involved in pigmentation variation, was identified. To our knowledge, this is the first report of the genetic locus for body colour variation in this species. These findings will be useful for the fine mapping of the determining gene for body colour variation of A. japonicus .